Write a Scientific Paper (WASP): Interdisciplinarity as it may become – As visualized in science fiction. (February 2019) - Grech, Victor
Abstract: Interdisciplinarity, the combining of two or more academic disciplines into one activity, is generally encouraged, but there are many pitfalls in the path of the would-be interdisciplinarian. Science fiction, has repeatedly warned of indulgence in super-specialization. This paper will review the genre's depiction of some protagonists who have reified the interdisciplinary paradigm within science fiction, and some lessons that may be learned from these narratives.